Electrospinning, preparation and characterization of polyvinylidene fluoride / pectin electrospun loaded with benzalkonium chloride as a drug reservoirs - Hamzah, Mohd Syahir Anwar; Ng, Celine; Abdul Sukora, Jumadi; Mohd Ali, Kamarul Syazwan; Mat Nayan, Nadirul Hasraf (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), 2021)
Porous nanofiber electrospun of polyvinylidene fluoride (PVDF)/pectin was successfully developed using electrospinning method containing benzalkonium chloride (BAC) as a drug model for the controlled drug delivery system assessment. The electrospun was tested for its mechanical, morphological, and wettability properties. Scanning electron microscope (SEM) micrograph demonstrated that the smooth surfaces of nanofibers morphology had achieved up to 2 wt% pectin inclusion with optimum fiber diameter, 143 ± 1.4 nm. The optimized scaffold PVDF/Pectin showed that the reduction of mechanical integrity and optimum value of tensile strength, modulus strength, and elongation at break were 5.98 ± 0.17 MPa, 16.82 ± 0.10 MPa, and 79.3 ± 1.3% MPa. Water contact angle analysis and degree of swelling suggested that inclusion of pectin had enhanced the wettability properties of hydrophobic PVDF electrospun with highest swelling capacity achieved of 78.9 ± 1.7%. The in vitro drug release tests using BAC, which was released from the hybrid electrospun nanofibers, achieved prolonged release profile due to elimination of the uncontrollable initial burst release. Kinetic release study from Higuchi Model and Korsmeyer-Peppas further validates that the drug release mechanism is only influenced by the diffusion factor. The present study indicates the potential of PVDF/pectin electrospun nanofibers to be exploited as a tool for sustainable drug delivery system.